An Overview of Midwives’ Knowledge Regarding the Integrated Postpartum Care Management Chart in the Service Area of the Satui Community Health Center, Satui Subdistrict, Tanah Bumbu Regency, South Kalimantan - Ratnawiyah Ratnawiyah; Dwi Rahmawati; Zulliati Zulliati; Novalia Widiya Ningrum (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Maternal Mortality Rate (MMR) is still a serious global and national health problem, including in Tanah Bumbu Regency, South Kalimantan, with bleeding and hypertension as the main causes. Effective postpartum services are very important, but the coverage of postpartum and KBPP visits at the Satui Care Health Center shows a decrease or fluctuation. Although the Minister of Health Regulation No. 21 of 2021 requires the use of integrated management charts during the postpartum period, the socialization of this chart/algorithm is not evenly distributed among midwives, has the potential to hinder early detection and management of complications, and contribute to AKI. This study aims to describe midwives' knowledge about the integrated management chart of postpartum services in the working area of the Satui Care Health Center, Tanah Bumbu Regency. This quantitative descriptive study involved 26 midwives as respondents from a population of 34 midwives who provided childbirth care, using the Purposive sampling method. Knowledge was measured by validated and reliable questionnaires (Cronbach's Alpha 0.933 for 15 valid items). The data was analyzed in univariate. The majority of midwives (57.69%) had "Sufficient", 23.08% "Good" and 19.23% "Less" knowledge regarding the integrated management chart of postpartum services. The knowledge of midwives in the work area of the Satui Care Health Center still needs to be improved, especially those with "lacking" knowledge. It emphasizes the importance of socialization and continuous training to optimize postpartum services and reduce AKI.